'A White Man Will Never Be a Zambian': Racialised Nationalism, the Rule of Law, and Competing Visions of Independent Zambia in the Case of Justice James Skinner, 1964–1969. Issue 3 (4th May 2019) - Sishuwa, Sishuwa
Abstract : Much of the existing historical work on politics in independent Zambia stresses the country's comparative lack of racial tension. However, this article argues that, as elsewhere in Africa, racial ideas were deployed in the early years after the achievement of independence in 1964 and found expression in the competing forms of nationalism that manifested themselves within the governing United National Independence Party. The article considers the case of James Skinner, a white Zambian of Irish descent and head of the country's judiciary, who in July 1969 was forced to resign after he supported the decision of a white High Court judge to acquit two white Portuguese soldiers who had illegally crossed into Zambia from Angola. Drawing on archival, newspaper and oral sources, I argue that the Skinner case was a touchstone for divergent intra-party visions of Zambia as an independent nation: visions that played out through racial and regional security considerations. Slogans deployed during the campaign to oust Skinner, most notably 'A white man will never be a Zambian', shed light on how the construction of Zambian political attitudes, national identity and citizenship became closely aligned with racial identities. Zambia was not the exception within southern Africa that it has commonly been assumed to be.